PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH, PEMANFAATAN TEKNOLOGI INFORMASI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada OPD Kabupaten Rokan Hilir) - Yuliza, Yuliza; Kennedy, Kennedy; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine the influence of the application of government accounting standards, the application of regional financial accounting system, the utilization of information technology, and internal control system to the quality of local government financial statements (Empirical Study on OPD of Rokan Hilir Regency). The results showed that the variable application of government accounting standards affect the quality of local financial statements. Furthermore, the variables of the regional financial accounting system have an effect on the quality of regional financial report. Furthermore variables utilization of information technology affect the quality of local financial statements. Furthermore, internal control system variables affect the quality of local financial statements. The results showed that the R Square value of 0.884. The meaning is that the contribution of variable application of government accounting standards, the application of regional financial accounting system, the utilization of information technology and internal control system to the quality of local financial statements is 88.4% While the remaining 11.6% is influenced by other variables not included in the model this research.Keywords : Application of government accounting standards, the application of regional financial accounting system, the utilization of information technology, internal control system, quality of local financial statements